Quality Control of Defective Products of Pucuk Harum Tea 350 ml Using the Seven Tools Method at PT. TFJ Pasuruan - salam (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2023)
The advancement of time has shifted consumer perspectives in product selection, where quality now plays a crucial role alongside competitive pricing. Achieving near-zero product defects requires significant investment through comprehensive improvements in both quality and production processes. PT. TFJ, a beverage manufacturing company established in 2012 and located on Jl. Raya Pasuruan-Malang, specializes in producing 350ml Teh Pucuk Harum. The company currently faces product defects such as loose caps, underfilled bottles, and dented bottles. This study applies the Seven Tools method to identify and analyze the root causes of these defects. The analysis reveals that the most dominant defect is the loose cap (66.69%), followed by underfilling (17.87%) and dents (15.43%). Proposed corrective actions include regular inspection and replacement of magnets, providing daily briefings and operator training, and testing new, higher-quality materials. These improvements aim to reduce product defects and enhance overall production quality.